Organising against all odds: Precarious workers as "actors and authors of their own drama" - Edlira Xhafa (International Labour Organization (ILO), 2019)
The insecurity and instability experienced by precarious workers, and their 'disconnect' from the established groups, are often intertwined in the perception that these workers are unorganisable. This paper challenges this perception through seven stories of collective organising, which show that pockets of collective resistance can emerge amongst various group of precarious workers, from both traditional and non-traditional sectors of the working class, despite the level of precarity and the level of repression and hostility in the context where collective organising takes place. Building on Kelly's mobilisation theory, this paper suggests four factors which facilitate the emergence of collective acts of (transformative) organising: a) an employer's concrete act of worsening working conditions which are experienced by workers as an infringement of their dignity; (b) a context of successful organising stories and/or visible trade unions/workers' organisations; (c) an organisation engaging in an empowering repertoire of collective action; and (d) a transformational leadership framing workers' struggles in broader class-societal terms. Generally speaking, in the presence of some sort of structures, the first two conditions are sufficient to facilitate the emergence of temporary acts of collective resistance by precarious workers. The other two conditions, however, are fundamental to transformative organising. They involve a shift from organising as a temporary strategy of addressing grievances and winning recognition for collective bargaining to organising as a long-term intentional political project of building independent worker power to advance a vision of social justice. By developing precarious workers into organic leaders and by constructing axes of solidarity across the highly mobile and fragmented precariat and beyond, transformative organising provides the space for empowering these workers to become not only actors, but potentially also authors of their own drama.
Keywords: 330